Gonadal Function Recovery in Patients With Advanced Hodgkin Lymphoma Treated With a PET-Adapted Regimen: Prospective Analysis of a Randomized Phase III Trial (AHL2011). Issue 29 (10th October 2021) - Demeestere, Isabelle; Racape, Judith; Dechene, Julie; Dupuis, Jehan; Morschhauser, Franck; De Wilde, Virginie; Lazarovici, Julien; Ghesquieres, Hervé; Touati, Mohamed; Sibon, David; Alexis, Magda; Gac, Anne-Claire; et al.
Abstract : PURPOSE: The prospective, randomized AHL2011 trial demonstrated that the use of the doxorubicin, bleomycin, vinblastine, and dacarbazine regimen (ABVD) after two cycles of bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone (BEACOPPescalated ) in early responders on the basis of a positron emission tomography (PET)–driven strategy was safe and minimized toxicity compared with standard 6 BEACOPPescalated cycles. This substudy investigated the benefit of this strategy in gonadal function and fertility in patients under 45 years old. METHODS: Ovarian function was assessed by serum measurement of follicle-stimulating hormone (FSH), estradiol, and anti-müllerian hormone in women, and semen analysis, FSH, and testosterone levels were used to evaluate testicular function in men at baseline, end of treatment, and during 5 years of follow-up. RESULTS: A total of 145 women and 424 men, enrolled between May 19, 2011, and April 29, 2014, were included. The risk of premature ovarian insufficiency (FSH > 24 IU/L) and of having a low ovarian reserve (anti-müllerian hormone < 0.5 ng/mL) was reduced after treatment in the PET-driven group (odds ratio [OR], 0.20; 95% CI, 0.08 to 0.50; P = .001 and OR, 0.15; 95% CI, 0.04 to 0.56, P = .005, respectively). Both parameters were correlated with age and dose of alkylating agents. However, no significant differences were observed in terms of pregnancy rates. Men in the PET-driven group had a higher recovery rate of sperm parameters after treatment compared with the standard BEACOPPescalated group, as well as a lower risk of severe testicular damage (OR, 0.26; 95% CI, 0.13 to 0.5; P < .0001) and a higher likelihood of achieving pregnancy (OR, 3.7; 95% CI, 1.4 to 9.3; P = .004). CONCLUSION: Although both treatments affected ovarian reserve and spermatogenesis, the PET-driven strategy decreased the risk of gonadal dysfunction and infertility in advanced Hodgkin lymphoma.